The evaluation of the experimentation protocol. - Preziosi, Paolo (Medicina e Morale, 1998)
In this article the Author indicates the criteria on the basis of which it is necessary to evaluate a protocol of experimentation with human subjects. The analysis of the protocols has to consider the research plan, the researchers involved, the subjects participating, the information that is given to the participants. The research plan has to provide a general vision of the project proposed, which should be clear and unequivocal and should concentrate particularly on the experimental plan and the methodologies, the place where the research will take place, the center of reference, the duration, the analysis of the data; the researchers involved in the research will have to be indicated by name and qualification (the same criterion is valid for whoever is responsible for the assistance of the patients included in the experimentation and for the person responsible for the experimentation team). The subjects participating in the study will have to be recruited with an accurate evaluation, specifying their number, the modalities of recruitment, their relationship with the researcher, their vulnerability, the criteria of inclusion and exclusion, the risks. The information will have to be clear in order to allow for valid, informed and voluntary consent. The final part of the article also mentions the problems that one can come across with subjects who participate in clinical experimentation as healthy volunteers and those regarding voluntary patients.